¿las emociones discretas permiten distinguir entre las infracciones convencionales y morales? (2020)
This research analyzes the relationship between emotion and the distinction in violation of moral and conventional norms, from a first and third person perspective. A questionnaire was conducted in Qualtrics where different hypothetical scenarios of infringement of these norms were presented: 3 conventional scenarios and 3 moral scenarios, each one in both perspectives (first and third person), where questions associated with emotional responses, permissibility and morality in every setting were presented later. We worked with a sample of 198 people between 18 and 71 years old, using a convenience sampling. The data analysis conducted consisted of frequency tables, 4 ANOVAS and 2 linear regressions. The results indicated that the violations of the conventional scenarios are scored significantly as more permissible and morally correct than the moral scenarios; The emotion? Satisfaction? for being the only? positive? significantly predicts a higher permissibility and morality score than the other emotions; The intensity of the emotion predicts the score for both Morality and Permissibility in an inversely proportional manner and age significantly predicts, although with a minimal value, the permissibility of infractions in an inversely proportional manner regardless of the type of scenario. The general conclusion of the study seen in the results is that the intensity of the emotion and the type of scenario do predict the score in permissibility and morality of the infractions.